A rare case of unicornuate uterus with non-communicating functional rudimentary horn associated with grade 3 endometriosis and a vascular anomaly - Rajashekara, Shruthi Kelasur; Ajjammanavar, Virupaksha; Sambashivaiah, Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Uterine anomalies result from either non-fusion or aberration in the fusion of the Müllerian ducts. An unicornuate uterus is one such anomaly that can present in different age groups due to its variation in relation to the presence or absence of a rudimentary horn. It can present as severe dysmenorrhea in young women if there is hematometra in the non-communicating functional rudimentary horn or if there is associated endometriosis. It can also present with infertility, recurrent pregnancy loss, or preterm delivery, and can be incidentally diagnosed during a cesarean section. One of the dreaded complications is pregnancy in the non-communicating horn and its rupture. It can pose a diagnostic and management challenge. Magnetic resonance imaging (MRI) is the gold standard for diagnosis, and surgical management is imperative in case of a functional non-communicating horn for relief of dysmenorrhea, prevention of endometriosis, and to prevent pregnancy complications. We report a case of a woman in her early 20s with severe dysmenorrhea and infertility diagnosed with a unicornuate uterus with a non-communicating functional rudimentary horn with grade 3 endometriosis with vascular anomaly who was managed surgically.